Natureza e arquitectura : notas a pretexto do atual interesse pela sustentabilidade - Silva, Bruno (2014)
The term “natural” certainly could not be used while nature was not understood and presented as an object of knowledge and experience, defend Ábalos and Herreros. In “Nature and Architecture”, Paolo Portoghesi refers the differences and similarities between the natural forms and architectural forms, but also draws attention to the comparisons between natural forms and ideas that over the centuries have marked the architecture. There was always a distinction between “natural” and “artificial”, as well as between science of architecture and art of architecture. Science communicates notions of quantity, verifiable by number and universal reading. On the other hand, the art communicates concepts of value and fantasy. This is how Jacinto Rodrigues quotes Arne Klingborg saying that the profound experience of nature is expressed in artist and poets, seeking images or “beings of nature that manifest themselves ,as we know now, through the tales of folklore and ancient poetry". Admittedly, the architecture is affected by issues that fill the pages of newspapers and broadcast media in this discipline. One theme that most emerges is, undoubtedly, the sustainability and / or eco-architecture. In this framework, we will discuss the ecology as a scientific discipline of architecture. We want to recognize the central role of ecology and the purposes of science, especially the one that goes by the name of “new paradigm” in order to show to architecture how continuity and innovation can finally be together. It is because of this innovation and technological advances that architecture and man seem to forget the dependence of Nature.